The Influence Brand Identity, Brand Leadership, and Brand Comunication toward Job Satisfaction - Rini Safitri; Feri Dwi Riyanto; Indah Yuliana (Department of Management, Faculty of Economics and Business, Brawijaya University, 2020)
Employees are pivotal resources for the organization as their various interactions among many levels in the employment experience that led to strong brands. Brand identity is the foundation in employer marketing that complement in training, social event, and mentor programs.. In this research, survey were conducted in telecommunication industry resulting 165 employee responses. Smart PLS was done to test the hypotheses, resulting that brand identity, brand leadership and brand communication influenced job satisfaction. This finding is in line with previous research where branding technique by employer not only cause employee turnover to drop, but also create benefits such as increased employee satisfaction, customer satisfaction and loyalty, and a positive image among other stakeholders. It is suggested that organization to promote employer branding includes brand identity, brand leadership, and brand communication for future business strategies.